The exclusionary side of (women's) social citizenship in Southeastern Europe: childcare policy development in Bosnia-Herzegovina and gender, social and territorial inequalities - Dobrotić, I; Obradović, N (Taylor and Francis, 2020)
The article explores the shifts in (women’s) social citizenship in Bosnia-Herzegovina and its effect on the development of childcare policy in the 1945–2019 period. Gendered, selective childcare policy, which was inherent in the socialist notion of social citizenship and aimed to emancipate women as ‘worker-mothers’, deteriorated in the transition period when ethnicity became prioritized over gender and class. Exclusionary citizenship practices increased with the post-1990 reforms as gender and social inequalities incorporated into childcare policy design become intertwined with inequalities based on ethnicity and/or locality. The post-1990 period is characterized by discontinuity, retrenchment and weak implementation of childcare-related rights.